Strategies to control aflatoxin in groundnut value chains - Florkowski, Wojciech J.; Kolavalli, Shashidhara (International Food Policy Research Institute, 2014)
Groundnuts, which are widely consumed in West Africa, are prone to contamination by aflatoxin during production and storage. Although aflatoxin plays a role in many of the important health risks in developing countries, individuals and governments ignore the risks because their health effects are not immediate. In the developed world strong regulations remove contaminated kernels and their products from the food systems. The objective of this paper is to examine production and marketing practices, particularly grading methods, in Ghana’s groundnut value chain to obtain a clear understanding of the sources and levels of aflatoxin contamination in the crop and how such contamination can be sharply reduced.